EFFECT OF RECRUITMENT PROCESSES, PLACEMENTS, WORK EXPERIENCE AND EMPLOYEE DISCIPLINE ON EMPLOYEE WORK ACHIEVEMENT IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF KARIMUN DISTRICT IN 2020 - Hutasoit, Hasudungan; Syahril, Syahril; Andykhatria, Andykhatria; Almansa Fitra, Mohamad; Indrayani, Indrayani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to determine: (1) the effect of the recruitment process on employee job performance at the Population and Civil Registration Service, (2) the effect of employee placement on employee performance at the Population and Civil Registration Service, (3) the effect of employee discipline on achievement Employee work at the Department of Population and Civil Registration, (4) the effect of work experience on employee performance at the Department of Population and Civil Registration, (5) the effect of the recruitment process on the placement of staff at the Department of Population and Civil Registration, (6) the effect of the recruitment process on employee discipline at the Department of Population and Civil Registration, (7) the effect of the recruitment process on work experience at the Department of Population and Civil Registration, (8) the effect of employee placement on work discipline at the Department of Population and Civil Registration, (9) the effect of employee placement on work experience at the Office Citizenship and Civil Registration, (10) the influence of employee discipline on work experience at the Department of Population and Civil Registration, (11) the effect of the recruitment process, placement, employee discipline and work experience on employee work performance at the Population and Civil Registration Service, (12) the effect of the recruitment process on employee placement through employee job performance at the Population and Civil Registration Service. This study uses research. quantitative by associative method. The data collection techniques in this study were questionnaires and interviews. The sampling technique used was probability sampling technique, namely stratified random sampling at the Department of Population and Civil Registration with a total of 50 respondents. The validity and reliability of the questionnaire data have been tested.